Attribution of weather and climate events - Otto, F (Annual Reviews, 2017)
Within the last decade the attribution of extreme weather and climate events has emerged from a theoretical possibility into a subfield of climate science in its own right providing scientific evidence on the role of anthropogenic climate change in individual extreme weather events on a regular basis using a range of approaches. Different approaches and thus different framings of the attribution question lead to very different assessments of the role of human-induced climate change. While there is no right or wrong approach the community is currently debating what are appropriate methodologies depending on stakeholder needs and scientific limitations. Tackling these limitations with more thorough model evaluation and meaningful bias corrections as well as going from the meteorological hazard to attributing the true impacts of extreme weather are the main challenges to face in the coming years.